The collected poems of W.B. Yeats - Yeats, W. B. (William Butler), 1865-1939; Finneran, Richard J (New York : Scribner Paperback Poetry, 1996)
Gathers all of the poems by the Irish writer, including reworkings of Irish myths and meditations on youth, love, nature, art, and war
Lyrical. Crossways (1889) -- The rose (1893) -- The wind among the reeds (1899) -- In the seven woods (1904) -- The green helmet and other poems (1910) -- Responsibilities (1914) -- The wild swans of Coole (1919) Michael Robartes and the dancer (1921) -- The tower (1928) -- The winding stair and other poems (1933) -- [Parnell's funeral and other poems (1935)] -- New poems (1938) -- [Last poems (1938-1939)] -- Narrative and dramatic
Includes bibliographical references and indexes
Keywords: Poetry